2019
DOI: 10.3390/ijms21010292
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Pathways Associated with Patterned Cerebellar Purkinje Neuron Degeneration in Niemann-Pick Disease, Type C1

Abstract: Niemann-Pick disease, type C1 (NPC1) is a lysosomal disease characterized by progressive cerebellar ataxia. In NPC1, a defect in cholesterol transport leads to endolysosomal storage of cholesterol and decreased cholesterol bioavailability. Purkinje neurons are sensitive to the loss of NPC1 function. However, degeneration of Purkinje neurons is not uniform. They are typically lost in an anterior-to-posterior gradient with neurons in lobule X being resistant to neurodegeneration. To gain mechanistic insight into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 106 publications
(128 reference statements)
5
23
1
Order By: Relevance
“…We suspected that the clustering might be related to location of the Purkinje neurons in the cerebellum, since Purkinje neurons in anterior lobules (I to VI) are substantially lost by seven weeks of age. Classification of these two clusters as anterior and posterior Purkinje neurons ( Figure S5B) is supported by prior data and the Allen Brain Atlas [20,41]. Calb1 and Car8, known Purkinje neuron markers, show uniform expression, whereas Sv2c and Abdh3 show decreased and Car7 and B3galt5 [42] show increased expression in posterior Purkinje neurons ( Figure S5C).…”
Section: Neuronal Transcriptomessupporting
confidence: 71%
See 1 more Smart Citation
“…We suspected that the clustering might be related to location of the Purkinje neurons in the cerebellum, since Purkinje neurons in anterior lobules (I to VI) are substantially lost by seven weeks of age. Classification of these two clusters as anterior and posterior Purkinje neurons ( Figure S5B) is supported by prior data and the Allen Brain Atlas [20,41]. Calb1 and Car8, known Purkinje neuron markers, show uniform expression, whereas Sv2c and Abdh3 show decreased and Car7 and B3galt5 [42] show increased expression in posterior Purkinje neurons ( Figure S5C).…”
Section: Neuronal Transcriptomessupporting
confidence: 71%
“…Npc1 expression in astrocytes significantly increases survival for Npc1 −/− mice, suggesting glial cells dysfunction is involved in disease progression [17]. Differences in RNA expression between control and mutant tissue can be used to obtain insight into biological processes that are altered in the disease state, and groups have compared cerebellar transcriptomes between control and NPC1 mutant mice at different ages [18][19][20][21]. However, transcriptome analysis of intact tissue/lobules mask potentially significant expression changes at the individual cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…Our studies however have shown that PCSK9 does not appear to play a role in NPC1 pathology even though we found expression differences in the lobules susceptible and resistant to Purkinje neuron death [16]. In all parameters measured (disease severity score, weight, lifespan, selected motor functions and Purkinje neuron staining and serum liver enzymes), we did not discern an obvious difference in NPC1 disease progression in mice with or without PCSK9.…”
Section: Discussioncontrasting
confidence: 81%
“…Immunostaining of calbindin, as a specific marker for Purkinje neurons, in cerebellar sections from 7-week old Npc1 +/+ /Pcsk9 -/mice showed an intact distribution of Purkinje neurons throughout the lobules of the cerebellum ( Figure 4A). This pattern is consistent with a healthy cerebellar phenotype with respect to Purkinje neurons [16] and demonstrates that lack of Pcsk9 did not appear to affect these neurons in Npc1 +/+ mice although subtle changes may have occurred that were not observed. In contrast, staining from 7-week old Npc1 -/-/Pcsk9 -/mice showed a significant reduction of Purkinje neurons in the anterior lobules of the cerebellum ( Figure 4B), consistent with the expected Purkinje neuron loss at this age during disease progression of NPC [16].…”
Section: Cerebellar Analysis Of Purkinje Neurons By Immunohistochemicsupporting
confidence: 82%
See 1 more Smart Citation